Description of two new genera (Antarctotetilla, Levantiniella) and a new species of Tetillidae - Carella, M.; Uriz, M.J. (Zootaxa, 2018)
Tetillidae is a sponge family distributed all over the world but with some genera apparently endemic from the Antarctic and Subantarctic (the “Antarctic clade”). Species identification results tricky due to the similarities of their morphological characters. However, molecular phylogenies have helped to resolve the family taxonomy. The last phylogenetic study on Tetillidae suggested the creation of two new genera: Levantiniella and Antarctotetilla. Lenvantiniella, from Middle East Mediterranean Sea, was previously classified within Cinachyrella, from which it differs in the small rounded surface cavities, distinctive from true porocalices. Antarctotetilla has up to now an Antarctic distribution, and harbors species wrongly classified within Tethya, Craniella, or Tetilla. The main differences of Antarctotetilla to other Tetillidae genera are the presence of pores grouped in small areas, and a poorly-defined cortex (pseudocortex). This study aims to re-describe in detail the species of Tetillidae that belong in the two above mentioned new genera, and to highlight that molecular phylogenies should be combined with morphological analyses to improve taxonomical decisions. We also describe a new Tetillidae species with a hair-like hispidation, which we name Antarctotetilla pilosa nov. sp. Furthermore, the types of Tethya coactifera and T. crassispicula (Lendenfeld, 1907) were reexamined because of some morphological similarities with Antarctotetilla. The minibarcode sequences (a small COI fragment) placed them within the Antarctic clade harboring Antarctotetilla and Cinachyra, but did not resolve their genus position. A morphological revision, however, suggests placing T. coactifera in Antarctotetilla, while T. crassispicula, which owns porocalices and a spicule-reinforced cortex, appeared to belong in Cinachyra.